Overweight and obesity among Australian children and adolescents - (:unkn) unknown (Australian Institute of Health and Welfare, 2020)
Overweight and obesity affects 25% of Australian children and adolescents, and is associated with poorer health and wellbeing and higher health-care costs. Some children and adolescents are more likely to be overweight or obese, such as Indigenous children and children living in disadvantaged areas. Many factors contribute to the development of overweight and obesity, including environmental influences and individual behaviours.
Keywords: Adolescents and youth; Childhood and child development; Health and wellbeing